Examining the influence of brand personality dimension on consumer buying decision: evidence from Ghana - Attor Cleophas; Jibril Abdul Bashiru; Amoah John; Chovancova Miloslava (Management şi Marketing, 2022)
With the advent of innovative marketing, the increasing use of brand personality concepts for the promotion of a brand or product has received scholarly work across the globe. Yet little is known in the literature about the dimensions of brand personality and its applicability in the telecommunication industry. Considering the known link between brand personality and customer purchase intent, this research sought to examine the impact of the brand personality dimension on customer buying decisions in the telecoms sector. A positivist research paradigm was used to attain the study goal(s) with valid data of 414 subscribers (customers) of telecom giants in Ghana. The result from the PLS-SEM technique identified five main attributes of brand personality (ie. sincerity, excitement, competence, sophistication, and ruggedness) as antecedents of customer buying decisions in the research model. Findings revealed that brand sincerity, brand excitement, and brand competence have a significant relationship with customer buying decisions. Whereas brand sophistication and ruggedness were not. An effective brand increases its brand equity by having a consistent set of traits that a specific consumer segment enjoys. This article not only provides empirical insight into the brand personality literature but also serves as a source of information for managers in the telecom industry to successfully trigger strategic marketing practices that would help to optimize the usefulness of the brand personality concept. Limitations and future research directions are discussed.